Study of Electrical Conductivity and Microcosmic Structure of Tetrahedral Amorphous Carbon Films Doped by Boron - Xiaoyan Wang; Yuqing Zhao (Advances in Materials Science and Engineering, 2015)
A type of tetrahedral amorphous carbon (ta-C) film that was doped by boron (ta-C:B) is focused on in this paper. The ta-C film is prepared by filtered cathodic vacuum arc (FCVA) technique and then doped with boron using the thermal diffusion method. Then the microcosmic structure and electrical conductivity of the ta-C are characterized by an X-ray photoelectron spectroscopy (XPS) method and four-probe method, respectively. The results show that the conductivity of ta-C:B is significantly increased; the resistivity decreases from 1.5 × 106 Ω·cm to 350 Ω·cm approximately, while the percentage of sp3 bonds in the film is changed from 87% to 60% approximately. It means that this type of film preserved the mechanical characteristics of diamond-like carbon (DLC) films and improved the electrical characteristics greatly at the same time.